Multilateralising preferential rules of origin around the world - Antoni Estevadeordal; Jeremy Harris; Kati Suominen (Inter-American Development Bank (IDB), 2009)
This paper maps out Rules of Origin (RoO) in regional trade agreements (RTAs) around the world, and observes that the restrictiveness and complexity of RoO are driven by factors specific to each RTA, including economy size and level of development. Given the powerful political economy forces that generate and determine the origin regime, harmonization, insofar as this means requiring identical rules for unconnected RTAs, is not practical and could be counterproductive. However, one can imagine rules that, if agreed at the multilateral level, could help limit the distortions caused by the RoO of the everincreasing number of RTAs. This would be a process of 'multilateralising' preferential RoO. Furthermore, there are mechanisms that could allow regions with particularly dense networks of overlapping RTAs (for example the Americas and, increasingly, Asia) to replace the spaghetti bowl with something more like a plate of lasagne. This would be a process of 'convergence' of RoO. Finally, these two approaches can and should be mutually reinforcing: convergence regimes should be established within the framework and limitations of multilateral rules, whereas the multilateral rules should be established in a way that promotes and facilitates the negotiation of such regimes.
hdl:11319/2521
Keywords: 330